The Influence of Price, Brand Image, and Product Quality on Purchasing Intention in Indomie Consumers in The City of Surabaya - Putri, Helvy Novia (Lentera Barasaki Publishing House, 2023)
This research is focused primarily on the relationship between price, brand image, and product quality and purchase intention